The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.4103/1119-3077.113474
|View full text |Cite
|
Sign up to set email alerts
|

Isolated gallbladder rupture following blunt abdominal trauma

Abstract: The gallbladder is a relatively well-protected organ; consequently its rupture following blunt abdominal injury is rare and usually associated with other visceral injuries. Isolated gallbladder rupture is extremely rare. We report a healthy Nigerian adult male who sustained isolated gallbladder rupture following blunt abdominal injury from riding a motor cycle (Okada). A high index of suspicion with positive bile aspirate might lead to early diagnosis. Open cholecystectomy is a safe option of treatment in a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…A thin walled GB us more prone to rupture from blunt trauma than a diseased GB which is thick and fibrotic due to chronic inflammation. 3 GB perforation almost always occurs in a distended GB. Our patient had his last meal about 8 hours before the trauma making him more vulnerable to GB injury.…”
Section: Discussionmentioning
confidence: 99%
“…A thin walled GB us more prone to rupture from blunt trauma than a diseased GB which is thick and fibrotic due to chronic inflammation. 3 GB perforation almost always occurs in a distended GB. Our patient had his last meal about 8 hours before the trauma making him more vulnerable to GB injury.…”
Section: Discussionmentioning
confidence: 99%
“…7 Gallbladder perforation of such nature have mainly been reported in male patients as seen in this report. [8][9] The reason for such a perforation could be the time the patient was squeezed, corresponding to early morning where the stomach is empty, and the gallbladder is usually distended. 5 A study conducted in 1981 showed that post-prandially, the cholecystokinin levels increase, leading to constriction of the gallbladder.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the current case patient with associated grade II liver injury presented a blood pressure of 80/50 mmHg before resuscitation. However, isolated gallbladder injuries are reported in the literature (4)(5)(6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
“…A distended thin walled gallbladder is prone to injury. This distension could be due to prolonged starvation or increased tone of the sphincter of Oddi secondary to alcohol ingestion (3,5,6). Alcohol stimulates gastrin and secretin release which in turn increase bile flow in the setting of a highly toned Sphincter of Oddi.…”
Section: Discussionmentioning
confidence: 99%